Faktor-Faktor Yang Mempengaruhi Minat Menggunakan Cloud Accounting Pada UMKM Di Kota Pekanbaru - Putri, Sakina Aidul; Azmi , Zul; Rodiah , Siti (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
With the development of the times, information technology has influenced modern accounting practices, bringing process automation, increased data accuracy, and higher operational efficiency. Cloud accounting has emerged as a solution that is considered more suitable for MSMEs because it offers simplicity, more affordable costs, and flexible internet-based access. This study aims to examine the influence of performance expectations, business expectations, social influence, facilitating conditions, hedonistic motivation, and price value on the interest in using cloud accounting. The study was conducted on MSMEs in Pekanbaru. The sampling technique used was purposive sampling with a total of 96 respondents. The data collection method was a survey method using questionnaires. The data analysis technique in this study was multiple linear regression. The results showed that performance expectations, effort expectations, facilitating conditions, hedonistic motivation, and price value had a significant effect on interest in using cloud accounting, while social influence did not have a significant effect on interest in using cloud accounting among MSMEs in the city of Pekanbaru.